The vicious/virtuous circle debate in the Twenties and the Seventies - DE CECCO, M. (PSL Quarterly Review, 2013)
The vicious/virtuous circle debate is revived, and the recent debate which started in the mid-seventies is compared with that of the interwar period. The central issues are exchange rate depreciation, inflation and 'validating' monetary policy. The views of several economists are analysed, supported by quotations.